Dental eruption cyst: Case report - Rocafuerte-Acurio, Marco Antonio (2021)
Eruption cysts are benign lesions of soft tissue that appear on the mucosa of a tooth shortly before its eruption. These may go away on their own, but if they hurt, bleed, or become infected, they may require surgical treatment to expose the tooth and drain its content. We will present a case of an eruption cyst at the level of pieces 5.5 and 6.5 whose treatment was surgical in order to expose the crowns of the teeth. The objective of this article is to present the most relevant aspects related to this developmental alteration in order to achieve a correct diagnosis and provide an adequate treatment.